2022
DOI: 10.1002/jbm4.10705
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Vitamin D3 Supplementation on Acute Fracture Healing: A Phase II Screening Randomized Double‐Blind Controlled Trial

Abstract: Nearly half of adult fracture patients are vitamin D deficient (serum 25‐hydroxyvitamin D [25(OH)D] levels <20 ng/mL). Many surgeons advocate prescribing vitamin D supplements to improve fracture healing outcomes; however, data supporting the effectiveness of vitamin D 3 supplements to improve acute fracture healing are lacking. We tested the effectiveness of vitamin D 3 supplementation for improving tibia and femur fracture healing. We conducted a single‐center, d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 38 publications
(51 reference statements)
0
10
0
Order By: Relevance
“…A final total of 14 studies, assessing a total of 2734 patients, were included to assess fracture outcomes following vitamin D supplementation [ 10 , 14 , 23 34 ]. Nine of these were controlled trials of which seven were randomised and two were nonrandomised.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…A final total of 14 studies, assessing a total of 2734 patients, were included to assess fracture outcomes following vitamin D supplementation [ 10 , 14 , 23 34 ]. Nine of these were controlled trials of which seven were randomised and two were nonrandomised.…”
Section: Resultsmentioning
confidence: 99%
“…Five studies were cohort trials of which one was prospective and four were retrospective. One study identified in abstract form during the search was later published in full and also included in the analysis [ 34 ]. Table 1 summarizes the characteristics of the included studies, in order of the outcome investigated, and outlines the main findings.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations